SEASONAL FACTORS OF VISITING SHRINES OF FERGANA VALLEY REGIONS - Hamdamov son of Eldorbek Daniyorjon (Journals Park Publishing, 2024)
In this article, a number of shrines and shrines in the Ferghana Valley regions are described from a recreational and medical point of view, and at the same time, the seasonality of visiting these shrines is studied.
Keywords: Pilgrimage tourism, healing springs, healing sand, peak period, baud disease, jaundice, skin diseases.